2018
DOI: 10.1590/1982-4327e2832
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Validity of Zulliger-CS with the Social Skills Inventory for the Elderly

Abstract: Psychological evaluation instruments need to demonstrate their usefulness to respond to social problems and according to the reality of people. This study aimed to find evidence of convergent validity of the interpersonal relationship indicators and the cognitive triad of the Zulliger in the Comprehensive System (ZSC) with the Social Skills Inventory for the Elderly (IHSI Del-Prette). The sample consisted of 78 elderly individuals, between 60 and 96 years old (M = 76.07). As instruments, the sociodemographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…An assessment based on different psychological, selfreport and projective tests, observing significant convergences and divergences, which results in an interpretation that contextualizes the findings, provides an incremental and complementary view of individual psychological functioning (Bornstein, 2017). In this perspective, empirical studies demonstrate the validity and applicability of the Social Skills Inventory, IHS-Del-Prette in employment and health contexts (Del Prette et al, 2020;Grazziotin & Scortegagna, 2018). The basis of validity and reliability indicators for a current version of the Social Skills Inventory (IHS2-Del Prette) mainly consists of Brazilian and international publications of studies that used the previous version of the IHS-Del Prette (Del Prette et al, 2020;Del Prette & Del Prette, 2018).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…An assessment based on different psychological, selfreport and projective tests, observing significant convergences and divergences, which results in an interpretation that contextualizes the findings, provides an incremental and complementary view of individual psychological functioning (Bornstein, 2017). In this perspective, empirical studies demonstrate the validity and applicability of the Social Skills Inventory, IHS-Del-Prette in employment and health contexts (Del Prette et al, 2020;Grazziotin & Scortegagna, 2018). The basis of validity and reliability indicators for a current version of the Social Skills Inventory (IHS2-Del Prette) mainly consists of Brazilian and international publications of studies that used the previous version of the IHS-Del Prette (Del Prette et al, 2020;Del Prette & Del Prette, 2018).…”
mentioning
confidence: 96%
“…Recent literature reviews on ZSC (Cardoso et al, 2018;Grazziotin & Scortegagna, 2016) involving nonpatients (Grazziotin & Scortegagna, 2018;2021;Miguel et al, 2017) and based on contributions of Rorschach Performance Assessment System R-PAS (Gonçalves et al, 2019;Villemor-Amaral et al, 2016;Villemor-Amaral & Gomes, 2020) highlight the contributions and the need for advances in research on the psychometric properties of ZSC. It is noteworthy that studies on temporal stability are still rare, showing only the study by thus far.…”
mentioning
confidence: 99%
“…Some of the most relevant social skills for this population are expressing positive feelings, being able to ask for help from others, seeking information about the illness of the care-recip ient, and assertive communication (Pinto et al, 2016). Furthermore, evidence on the importance of these skills for caregivers shows that the burden experienced by such individual is related to a concentration of several care tasks in a single person (Grazziotin & Scortegagna, 2018;Pereira & Soares, 2015). According to the authors, this feeling could be mitigated by sharing these tasks, which could be agreed based on good quality interpersonal relationships.…”
mentioning
confidence: 99%
“…Some studies have demonstrated the contributions of the ZSC and the limitations of its use in the personality assessment, both at the international level (Aguilar & Graso, 2015;Carpio & Lugón, 2011;Contreras-Milián, González-Pérez, & Herrera-Espinosa, 2016) as well as in the Brazilian context (Cardoso, Gomes, Pacheco, & Viana, 2018;Grazziotin & Scortegagna, 2016a;2016b;Gregoletti & Scortegagna, 2017;Miguel, Zuanazzi, & Villemor-Amaral, 2017;Rien, Scortegagna, Grazziotin, & Bertolin, 2017). However, studies that address cognition in healthy adults (Grazziotin & Scortegagna, 2016a; and those that include older and long-lived adults are rare (Aguilar & Graso, 2015;Grazziotin & Scortegagna, 2018). Aguilar and Graso (2015) evaluated the cognitive functioning of elderly and long-lived adults using ZSC and neuropsychological instruments (MMSE, clocks test).…”
mentioning
confidence: 99%
“…Considering the relevance of instruments for psychological assessment in the elderly, Grazziotin and Scortegagna (2018) sought evidence of convergent validity of the interpersonal relationship and cognitive triad indicators of the ZSC with the Social Skills Inventory for the Elderly (IHSI-Del-Prette; Del Prette & Del Prette, 2001) with semantic and content adaptations (Carneiro et al, 2007;Scheufler et al,2016). The study comprised 78 elderly, non-patients, between 60 and 96 years (M = 76.07).…”
mentioning
confidence: 99%